Արցախի ազատության անմոռաց ջահակիրը - Բալայան, Ռոնա («Դիզակ պլյուս» հրատարակչություն)
В статье представлена деятельность преданного передового бойца арцахского национально-освободительного движения, его роль в создании национально-политической жизни новой независимой республики Арцаха. The article deals with the activity of the devoted fighter of Artsakh’s national liberation movement Arthur Mkrtchyan in the developed severe conditions for Armenians of Artsakh, his role in creation of the national political life of the new independent republic of Artsakh is presented.
Keywords: Պատմություն